The Effect of Implementing the SQ3R Learning Model Assisted by Card Media on Elementary School Students Reading Comprehension Skills - Abdah Birrul Walidain; Yayan Nurbayan; Wina Mustikaati (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
The low reading and text comprehension skills among elementary school students call for an innovative learning model capable of actively engaging students in understanding reading texts. This study aims to analyze the effect of implementing the SQ3R learning model supported by card media on students’ reading and text comprehension skills. This study employed a quasi-experimental method using a nonequivalent control group design, conducted at SDN 2 Nagrikaler Purwakarta with fifth-grade students divided into an experimental class and a control class. Data collection techniques included pre-tests, post-tests, observations, and documentation. The results of the study indicate that the implementation of the SQ3R learning model with the aid of card media is capable of improving students’ ability to identify main ideas, understand explicit and implicit information, answer questions based on the text content, and draw conclusions from expository texts. Statistical analysis revealed a significant difference between the experimental and control classes, with the model contributing 56.1% to the improvement in students’ reading comprehension skills. Therefore, the SQ3R learning model supported by card media is recommended as an interactive and innovative learning strategy for Indonesian language instruction in elementary schools.